Factors influencing the training of high school tutors for mental health care - Pérez-Pimienta, Diana; Ruiz Bernés, Salvador; Castillo Castañeda, Georgina; Pérez Sánchez, Lucía (Pensando Psicología, 2025)
Introduction. In recent years, the need to address emotional situations in students at different educational levels has become undeniable.Objective. The objective of this study is to analyze the factors that influence high school tutors’ acquisition of mental health knowledge, considering their perception of their ability and preparation for crisis response.Method. A quantitative, cross-sectional, descriptive-correlational design was used with a non-probabilistic sample of typical cases consisting of 228 high school tutors from 15 public high schools in the state of Nayarit (Mexico), ranging in age from 23 to 70 years.Results. The results indicated a common need to provide psychological support to students, primarily for issues such as depression, anxiety, and academic stress. A moderate to low perception of knowledge about psychological first aid was also evident, as well as a lack of formal training in this area among the participants. It was also observed that training and certain specific knowledge are positively associated with the development of mental health practices, while age and other related knowledge show a negative association.Conclusions. In conclusion, the importance of strengthening teacher training in mental health and crisis management is highlighted to improve care and support for students in high school education.
Keywords: adolescents; crisis; tutor teachers; mental health